Mediastinal lymphadenopathy in patients undergoing cardiac transplant evaluation - Pastis, Jr, Nicholas J; Van Bakel, Adrian B; Brand, Timothy M; Ravenel, James G; Gilbert, Gregory E; Silvestri, Gerard A; Judson, Marc A (Chest, 2011)
We evaluated the association between hemodynamic parameters of chronic congestive heart failure (CHF) and mediastinal lymphadenopathy (MLA) in heart transplantation (HT) candidates and the effect of HT on MLA. We also described the results of lymph node (LN) biopsies of MLA in the patients. Patients who underwent HT evaluation over an 8-year period and had chest CT scans were evaluated retrospectively. Data collected included LN sizes pre-HT and post-HT, echocardiographic measurements, radionuclide-derived ejection fraction, and right-sided heart catheterization hemodynamics. MLA was defined as LNs > 1 cm in smallest dimension. Of 118 patients, 53 patients had MLA. MLA had weak statistically significant correlations with elevated mean pulmonary artery pressure (MPAP), mitral regurgitation (MR), tricuspid regurgitation (TR), right atrial pressure (RAP), and pulmonary capillary wedge pressure (PCWP). Thirty-six patients with MLA underwent HT, and nine of the 36 had post-HT chest CT scans. All nine patients showed a decrease in LN size post-HT (mean LN diameter pre-HT = 1.16 ± 0.137 cm, post-HT = 0.75 ± 0.32 cm). Seven of 53 patients with MLA underwent biopsies. Four had benign LNs, one had sarcoidosis, and two had lung cancer. MPAP, MR, TR, RAP, and PCWP had weak statistically significant correlations with MLA. HT led to regression of MLA in patients who underwent CT scans post-HT, implying that MLA is related to CHF. However, we also identified clinically important causes of MLA; therefore, biopsy should be considered if enlarged LNs fail to regress after maximal medical management of CHF.